SKAM som social utopi - Christensen, Christa Lykke (K&K - Kultur og Klasse, 2018)
In this article I discuss the Norwegian teen drama series Shame, broadcast by the public service broadcaster NRK 2015-2017. In the Scandinavian countries the series was targeted to a young audience around 16 years old but it became extremely popular among viewers of all ages, among men and women, and moreover, streaming made it available globally. The article discusses TV production for a youth audience within a public service and a commercial media system. The argument is that the series, expressing the ethos of social responsibility of Scandinavian public service broadcasting, represents a social utopia and that it in several ways has much in common with the long tradition for Scandinavian realistic drama production for young audiences. Thus, the article argues that the drama series of Shame is based on a narrative of inclusion – in contrast to popular TV-shows for a young audience on commercial channels, for instance reality gameshows, which are often based on a narrative of exclusion. The theoretical framework draws on Erving Goffman’s micro-sociological considerations of the social dramaturgy of face work, and is inspired by the theory of recognition by Axel Honneth. Analytically, the face work and interactions of the main characters of the Shame-series are used to exemplify how the drama series creates a narrative of inclusion while addressing critical issues such as face loss, emotional rejections, and shame. In conclusion, the series is an example of successful public service programming that is able to address young people.